Pengaturan Dan Implementasi Subsidi Biodiesel Indonesia-Uni Eropa Dalam Agreement On Subsidies And Countervailing Measures - Intan Griya Purnamasari (Lex Renaissance, 2021)
The World Trade Organization WTO plays a major role in carrying out rules on international trade such as the General Agreement on Tariffs and Trade (GATT). Meanwhile, the regulation regarding subsidies is regulated in Article XVI of the GATT and the Agreement on Subsidies and Countervailing Measures (SCM) in 1995. In international trade, subsidies are considered as a form of unfair competition, hence their use is limited. The objective of this research relates to the regulation and implementation of Indonesian biodiesel subsidies in the European Union which are reviewed based on SCM. The results of the study concluded that the European Union Commission found grants, tax breaks and raw materials below market prices for Indonesian biodiesel, which under Article 3 SCM, these subsidies are prohibited because grants, tax breaks and feedstocks below market prices are intended for Indonesian biodiesel exported products. Therefore, the application of subsidies by Indonesia to biodiesel is not in line with SCM.Key Words: Biodiesel; SCM 1995; subsidiesAbstrakOrganisasi Perdagangan Dunia WTO memainkan peran utama dalam menetapkan aturan internasional tentang perdagangan seperti Perjanjian Umum tentang Tarif dan Perdagangan (GATT). Sementara pengaturan mengenai subsidi diatur dalam Pasal XVI GATT dan Agreement on Subsidi and Countervailing Measures (SCM) tahun 1995. Dalam perdagangan internasional, subsidi dianggap sebagai bentuk persaingan curang, sehingga penggunaannya dibatasi. Pokok dalam penelitian ini berkaitan dengan pengaturan dan implementasi subsidi biodiesel Indonesia di Uni Eropa yang ditinjau berdasarkan SCM. Hasil penelitian menyimpulkan bahwa Komisi Uni Eropa menemukan hibah, potongan pajak dan bahan baku di bawah harga pasar bagi biodiesel Indonesia, yang berdasarkan Pasal 3 SCM, subsidi ini dilarang dikarenakan hibah, potongan pajak dan bahan baku di bawah harga pasar tersebut ditujukan untuk produk biodiesel Indonesia yang diekspor. Oleh karena itu, penerapan subsidi oleh Indonesia terhadap biodiesel belum sejalan dengan SCM.Kata Kunci: Biodiesel; SCM 1995; subsidi